Interactive Tests and Their Use in The Learning Process - Atoev Ekhtiyor Khudoyorovich (Periodica Journal, 2022)
At present, Word, Excel, PowerPoint programs have become everyday tools for science teachers. Another innovation that has entered the field of education is the introduction of iSpring applications in PowerPoint. These applications allow you to create animations in PowerPoint, create interactive tests
Keywords: Word Press; interactive; tests; video